Targeted therapy for idiopathic pulmonary fibrosis: a bibliometric analysis of 2004–2024 - Zhang, Xinlei; Yuan, Zengze; Shi, Xiawei; Yang, Junchao (Frontiers in Medicine, 2025)
BackgroundIdiopathic pulmonary fibrosis (IPF) is a progressive and irreversible interstitial lung disease characterized by high mortality rates. An expanding body of evidence highlights the critical role of targeted therapies in the management of IPF. Nevertheless, there is a paucity of bibliometric studies that have comprehensively assessed this domain. This study seeks to examine global literature production and research trends related to targeted therapies for IPF.MethodA literature search was conducted using the Web of Science Core Collection, encompassing publications from 2004 to 2024, focusing on targeted therapies for IPF. The bibliometric analysis utilized tools such as VOSviewer, CiteSpace, and the “bibliometrix” package in R.ResultsA total of 2,779 papers were included in the analysis, demonstrating a general trend of continuous growth in the number of publications over time. The United States contributed the highest number of publications, totaling 1,052, while France achieved the highest average citation rate at 75.74. The University of Michigan Medical School was the leading institution in terms of publication output, with 88 papers. Principal Investigator Naftali Kaminski was identified as the most prolific researcher in the field. The American Journal of Respiratory Cell and Molecular Biology emerged as the journal with the highest number of publications, featuring 98 articles. In recent years, the research has emerged surrounding targeted therapies for IPF, particularly focusing on agents such as TGF-β, pathogenesis, and autotaxin inhibitor.ConclusionIn this bibliometric study, we systematically analyze research trends related to targeted therapies for IPF, elucidating recent research frontiers and emerging directions. The selected keywords-idiopathic pulmonary fibrosis, targeted therapy, bibliometric analysis, transforming growth factor β, and autotaxin inhibitor—capture the essential aspects of this research domain. This analysis serves as a reference point for future investigations into targeted therapies.